2022
DOI: 10.1111/hex.13586
|View full text |Cite
|
Sign up to set email alerts
|

Embedding lived experience into mental health academic research organizations: Critical reflections

Abstract: Background: As part of a growing emphasis on engaging people with lived experience of mental health conditios in mental health research, there are increasing calls to consider and embed lived experience throughout academic research institutes. This extends beyond the engagement of lay patients and also considers the potential roles of academic researchers with lived experience. When the lived experience of academic researchers is applied to academic work, there is the potential to improve the relevance of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 35 publications
(103 reference statements)
0
11
0
Order By: Relevance
“…As such, we incorporate this language to maintain our link to these professional bodies. However, others have reported that the word ‘patient’ can pose a barrier to engagement with lived experience experts; by emphasizing illness or deficit rather than expertise, the term can be seen as undervaluing and disrespecting these individual's contributions to research and to the engagement process 43 . We spoke with three of the ongoing League members about this topic.…”
Section: Discussionmentioning
confidence: 99%
“…As such, we incorporate this language to maintain our link to these professional bodies. However, others have reported that the word ‘patient’ can pose a barrier to engagement with lived experience experts; by emphasizing illness or deficit rather than expertise, the term can be seen as undervaluing and disrespecting these individual's contributions to research and to the engagement process 43 . We spoke with three of the ongoing League members about this topic.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, more fundamental organizational changes are needed to underpin necessary changes to funding and research study approaches. Participants with lived experience and academic experts do not always “speak the same language” [ 136 ], so awareness of differences in expression and the need to work together to solve health problems is necessary to minimize the impact of power imbalances and promote coproduction [ 137 ]. This can be achieved by developing safe spaces to create and share knowledge [ 138 ] and allow for opportunities for researchers and participants with lived experience to learn and enrich their own expertise from the experience of informed participation and collaboration [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…The term ‘patient engagement’ is only used for clarity purposes as it is commonly used in health research. In response to the expressed preferences of our lived experience panel, we refer to people with lived experience engaged in research projects as PWLE instead of the term ‘patient’—this is for clarity purposes; it should be noted that researchers can also identify as PWLE and apply their lived experience to research 27,28 …”
Section: Methodsmentioning
confidence: 99%